Nuclear prompt gamma spectroscopy for range verification in ion-beam therapy - Dal Bello, Riccardo (2020)
Proton and heavier ions have a characteristic energy deposition profile presenting the maximum at the end of range of the primary particles. This feature potentially allows delivering highly conformal radiation therapy, depositing most of the dose in the target volume and sparing the healthy tissue surrounding it. Despite its expanding clinical application, several limitations still affect this technique and there are great opportunities for further improvement. This thesis addresses the issue of range uncertainties. Many factors influence the range of the primary particles. Due to the sharp spatial gradients of the dose distribution, even a small shift can lead to severe changes in the treatment quality. Countermeasures are usually adopted in clinical practice to make the dose delivery robust to such shifts at the price of obtaining sub-optimal treatment plans. This thesis aims to develop a preclinical prototype to measure on-line and in-vivo the position of the dose deposition. The technique is based on nuclear prompt gamma spectroscopy. In this work, we first proposed the use of a novel detector type. Then, we optimized through simulations and experimentally characterized the detector system. Finally, we experimentally demonstrated the measurement of the particles range with millimetric precision in clinically relevant conditions.